Implementasi Peraturan Walikota Semarang Nomor 7 Tahun 2013 tentang Peningkatan Pemberian ASI Eksklusif (Studi di Puskesmas Pegandan Kecamatan Gajahmungkur Kota Semarang) - Intifada, Silma; Subowo, Ari (Journal of Public Policy and Management Review, 2017)
Semarang City’s goverment impose the Program of Exclusive Breast Feeding by publishing the Semarang Mayor goverment’s regulation nomor 7 by 2013. The low attainment of breast feeding in Gajah Mungkur compare with the target Dinas Kesehatan and national target were the background of done this research. The research aimed to analyze the implementation process these regulation later on it could be deduced that efforts need to be made in order to be effective implementation. This research was used qualitative research with observation, interview, and documentation to collect the data. The result of this research showed that the mplementation these regulation about the incresing of Exclusive breast feeding in Gajah Mungkur subdistrict have not been appropriate with these regulation. This problem occur because of a shortage in terms of resources, funds and facilities, the breast milk exclusive group support, communication, coordination, training of the officers which insufficient and the social economic effect of the society. Based on that problems, are needed to do some efforts which can be started by give right communication and continue support for the cadre ASI exclusive, coordination among Clinic officers Pegangan with group target and implementing the policies so that effective implementation require these regulation.